Heating of Atomic Force Microscopy (AFM) cantilevers operating in liquid media under intense optical illumination - Tremoço, Frederico Henriques Antão Mendes (2021)
Atomic Force Microscopy (AFM) has been combined with many optical microscopy techniques to expand the applications and capabilities of both techniques. However, the intense illumination of AFM cantilevers can give rise to a significant temperature increase due to the light power absorption on the gold coating, which is undesirable, especially for live cell imaging. Computational simulations based on Finite-Difference Time-Domain (FDTD) simulations for electromagnetic wave propagation and absorption combined with a finite element method implementation for thermal simulations were used to study the temperature increase of AFM cantilevers exposed to wide-field and confocal fluorescence illumination. Our analysis is consistent with a previous study based on a 2D model of a bimetallic strip. It is also observed a strong dependency of the temperature increase on the confocal spot vertical position. In some simulation’s conditions close to experimental set-up configurations we predict with our simulations a temperature increase up to 13 degrees Celcius, a temperature increase which undoubtedly will have an impact on live cell imaging. We conclude that temperature increases induced by fluorescence excitation light in combined AFM-fluorescence microscopy set-ups can be significant in the sense that they might affect the biological sample under investigation. A proper design of the combined microscopy system is therefore highly recommendable to avoid any potential sample heating artefact.